Esthetical education in university students - Jesús Rodríguez-Cotorruelo; Yilán Lobo-Rodríguez (Universidad de Guantánamo, 2017)
Art as a form of social consciousness, allows man to reflect the reality of the world, assess it from the point of view of the artist and then materialize into a sensory image with an aesthetic value. It is also a manifestation of human activity, whereby a personal and selfless vision that interprets the real or imagined with different material resources is expressed. To value beauty as aesthetic category is a fundamentals aspect in the training of future professionals; and that is why this paper aims to present the essential aspects of aesthetics and its role in the training of university students.